Mongolia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Mongolia. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Mongolia discusses that economy growth accelerated to 8.6 percent in the first quarter of 2019, over fiscal balance turned into surplus in 2018, and gross international reserves have increased by USD 2 1/2 billion since 2016. The recovery stems from a stronger policy framework, significant official financing and a rebound in external demand. Notwithstanding the progress, Mongolia remains vulnerable to external shocks given its high debt levels and the economy's dependence on mineral exports. Structural reforms progressed in several key areas: the budget process is more resilient to political pressure and quasi-fiscal activities were curtailed. In order to achieve sustainable and inclusive growth, it is necessary to advance the current reform efforts by strengthening the rule-based fiscal policy framework, ensuring financial sector soundness and improving governance. Risks are tilted toward the downside in the near term. Shocks to mineral demand can lead to sharp fall in exports, weakening growth outlook and fiscal accounts. A slowdown in growth could trigger financial instability given still inadequate capital buffers at some banks and overindebted households.